PHD JOURNEY ON EDUCATIONAL MANAGEMENT IN TURKEY: FROM COURSES TO DISSERTATION - Uslu, Turgut; Özba?, Mehmet; Yalç?n, Sinan (International Journal of Evaluation and Research in Education (IJERE), 2020)
This study aims to determine the theoretical and applicational characteristics of the PhD education in educational manegement in Turkey based on the opinions of the PhD students. Qualitative research method was used in the study and the phenomenology pattern was utilized. It was conducted in Academic Year of 2017-2018. The structured interview form, developed by the researchers, was used in the study. 14 students, who were 7 women and 7 men and studying PhD in educational management in Turkey participated into the study. Findings of the study indicates that PhD courses of educational management are mainly based on student presentations and the evaluation of these courses are mostly made by homework, student presentations or article review rather than formal exams. Students defined the PhD qualification exam process as a tough but instrictive and they had a positive experience of thesis proposal process except from finding an original topic. The participants who completed the processes above rarely had difficulties in the thesis writing process.